2003
DOI: 10.1515/156939203322733273
|View full text |Cite
|
Sign up to set email alerts
|

Structural equivalence of s-tuples in random discrete sequences

Abstract: Recently there appeared a signi cant number of papers investigating structural properties of random discrete sequences. They provide a large group of results on structurallyequivalent intervals in such sequences. The goal of the present paper is to give a survey of the problems and the known results in this interesting area of discrete probability theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…Under the hypotheses of Corollary 2, for s 2 the asymptotic behaviour of the random variable 0 n and the random variable n , which is equal to the number of pairs of s-tuples with identical frequencies of symbols in a segment of the sequence X of length n C s 1, is different. It can be shown that the asymptotic behaviour of n is determined by neighbouring overlapping tuples, and under the hypotheses of Corollary 2 E n grows without bound (see [11]). The asymptotic behaviour of s in different domains of variation of the parameters s and N is studied in [14].…”
Section: Corollarymentioning
confidence: 99%
See 3 more Smart Citations
“…Under the hypotheses of Corollary 2, for s 2 the asymptotic behaviour of the random variable 0 n and the random variable n , which is equal to the number of pairs of s-tuples with identical frequencies of symbols in a segment of the sequence X of length n C s 1, is different. It can be shown that the asymptotic behaviour of n is determined by neighbouring overlapping tuples, and under the hypotheses of Corollary 2 E n grows without bound (see [11]). The asymptotic behaviour of s in different domains of variation of the parameters s and N is studied in [14].…”
Section: Corollarymentioning
confidence: 99%
“…The match of frequencies of symbols in s-tuples defines on the set A s the permutation equivalence relation (see [11]), which is a special case of the G-equivalence (see [13]). In other words, the match of frequencies of symbols in two tuples is equivalent to the match of these tuples up to permutation of symbols.…”
Section: Remarkmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with the problem about exact matches of tuples, we point out the direction related to the asymptotic behaviour of the number of pairs of structurally or permutationally equivalent tuples, which is under active development over the last decade (see [2,17,18] and the survey [12]). …”
Section: Introductionmentioning
confidence: 99%